2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090670
|View full text |Cite
|
Sign up to set email alerts
|

Modeling study of the failing heart and its interaction with an implantable rotary blood pump

Abstract: The effectiveness of clinical diagnosis and treatment of heart failure is a direct function of clinical signs that can be measured in a patient within cost and safety constraints. Large-scale mathematical modeling can be a key tool in revealing important, measurable clinical signs of heart failure, furthering medical understanding and development of treatment. In the first part of this study we have created two models of left heart failure diastolic and systolic, using our human cardiovascular-respiratory syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…2426 A higher rotational speed has short-term advantages in hemodynamics, but sometimes causes aortic insufficiency and right ventricular failure over the longer term. 2729 Thus, we hope the future study which demonstrates that amelioration of CI without increasing rotational speed is effective in improving exercise intolerance; modifying the CI with medications such as diuretics and pulmonary hypertension drugs. And, physical therapy is more actively recommended for patients with reduced CI.…”
Section: Discussionmentioning
confidence: 99%
“…2426 A higher rotational speed has short-term advantages in hemodynamics, but sometimes causes aortic insufficiency and right ventricular failure over the longer term. 2729 Thus, we hope the future study which demonstrates that amelioration of CI without increasing rotational speed is effective in improving exercise intolerance; modifying the CI with medications such as diuretics and pulmonary hypertension drugs. And, physical therapy is more actively recommended for patients with reduced CI.…”
Section: Discussionmentioning
confidence: 99%
“…A cardiovascular-respiratory modeling study using an implantable rotary blood pump demonstrated that reduced septal contribution with increasing pump speeds resulted in elevated RV work and mechanical dyssynchrony. 15 …”
Section: Definition and Incidence Of Right Ventricular Failure After mentioning
confidence: 99%
“…46 In an in silico cardiovascular-respiratory system model, increased LVAD pump speeds appear to reduce septal contribution to RV and LV ejection and increase RV work. 47 Finally, patients with more severe RV dysfunction may be more prone to LV suction with higher LVAD pump speeds. 48 …”
Section: Pathophysiology Of Post-lvad Right Ventricular Failurementioning
confidence: 99%